Evaluation of Radiological and Anatomical Features of Cervical Vertebrae in Adult Persian Cat - Peghah Derakhshi; Siamak Alizadeh; Mohammadreza Hosseinchi (Veterinary Medicine and Science)
ABSTRACT Background Radiographic studies of Persian cat's cervical vertebrae can provide us with valuable information used in identifying its anatomical features, investigating various species of Persian cats and evaluating their cervical pathologies. Objectives The present study aimed to investigate the anatomical and radiological features of cervical vertebrae in Persian cats to create a comprehensive and accurate reference for the normal range of cervical bones and joints that can be used for clinical decision‐making and interpretation of radiographic findings in these cats. Methods The present descriptive‐cross‐sectional study included 10 adult Persian cats, including 5 males and 5 females. All cats underwent radiography in the dorsoventral, ventrodorsal, left lateral and right lateral recumbency. Then, anatomical investigations were performed. Results According to our findings, Persian cats were different from other cat species in some cervical vertebral characteristics, which can be suggested as comparative anatomy in these species. The most important differences were as follows: the C3 and C7 had the lowest and highest spinous process height (SPH), respectively. The atlas had the highest transverse process width (TPW), which was significantly different with other cervical vertebrae (p ≤ 0.05). Moreover, the cervical vertebrae were not significantly different in vertical diameter of cranial vertebral foramen (VDCrVF) and transverse diameter of cranial vertebral foramen (TDCrVF) (p ≤ 0.05). The caudal surface of the atlantic vertebral arch had two dorsal and ventral tubercles. Also, the ventral crest of the axis was quite indistinct in the cranial part while becoming prominent in the caudal part. The C3 spinous process was a wide, small tubercle, while the C7 spinous process was extended vertically. Finally, the C6 transverse processes had a large ventrocranial tubercle forming a sagittal plate with cranial and caudal parts separated by a notch. Conclusion The accurate and comprehensive standard ranges obtained from the present study can be used for the interpretation of imaging results, clinical decision‐making, and finding the normal and abnormal sizes of the cervical vertebrae and their processes in Persian cats.